2020
DOI: 10.1186/s12870-020-02535-9
|View full text |Cite
|
Sign up to set email alerts
|

Plant performance of enhancing licorice with dual inoculating dark septate endophytes and Trichoderma viride mediated via effects on root development

Abstract: Background: This study aimed to assess whether licorice (Glycyrrhiza uralensis) can benefit from dual inoculation by Trichoderma viride and dark septate endophytes (DSE) isolated from other medicinal plants. Methods: First, we isolated and identified three DSE (Paraboeremia putaminum, Scytalidium lignicola, and Phoma herbarum) and Trichoderma viride from medicinal plants growing in farmland of China. Second, we investigated the influences of these three DSE on the performance of licorice at different T. viride… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 70 publications
3
15
0
1
Order By: Relevance
“…A series of single- and dual-inoculation experiments indicated that greater performance of plants were potentially obtained in multi-species than in single-species contexts ( Figure 2 ). This result, itself, is consistent with previous reports of enhanced plant growth by specific pairs of bacteria/fungi ( Han and Lee, 2006 ; Wang et al, 2011 ; Ważny et al, 2018 ; He et al, 2020 ). Meanwhile, our experiments on 78 combinations of fungi systematically suggested that pairs of microbes, each of which had greatly positive impacts on plant growth in single inoculations, could show minor effects on plants under multi-species conditions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A series of single- and dual-inoculation experiments indicated that greater performance of plants were potentially obtained in multi-species than in single-species contexts ( Figure 2 ). This result, itself, is consistent with previous reports of enhanced plant growth by specific pairs of bacteria/fungi ( Han and Lee, 2006 ; Wang et al, 2011 ; Ważny et al, 2018 ; He et al, 2020 ). Meanwhile, our experiments on 78 combinations of fungi systematically suggested that pairs of microbes, each of which had greatly positive impacts on plant growth in single inoculations, could show minor effects on plants under multi-species conditions.…”
Section: Discussionsupporting
confidence: 93%
“…One of the major challenges in utilizing plant-associated microbial functions is to design sets of microbial species/isolates ( Vorholt et al, 2017 ; Paredes et al, 2018 ; Toju et al, 2018a ; Wei et al, 2019 ). While a single microbial species or isolate can have specific functions in promoting plant growth, broader ranges of positive effects on plants are potentially obtained by introducing multiple microbial species/isolates ( Wang et al, 2011 ; Ważny et al, 2018 ; He et al, 2020 ). For example, a fungal species degrading organic nitrogen ( Newsham, 2011 ) and another fungus suppressing soil pathogens ( Vinale et al, 2008 ) may collectively provide plants with a broader spectrum of physiological functions than each of them alone, potentially having additive or synergistic effects on the growth of their hosts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). This result, itself, is consistent with previous reports of enhanced plant growth by specific pairs of bacteria/fungi (Han and Lee, 2006;Wang et al, 2011;Ważny et al, 2018;He et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…One of the major challenges in utilizing plant-associated microbiome functions is to design sets of microbial species/isolates (Vorholt et al, 2017;Paredes et al, 2018;Toju et al, 2018a;Wei et al, 2019). While a single microbial species or isolate can have specific functions in promoting plant growth, broader ranges of positive effects on plants are potentially obtained by introducing multiple microbial species/isolates (Wang et al, 2011;Ważny et al, 2018;He et al, 2020). For example, a fungal species degrading organic nitrogen (Newsham, 2011) and that suppressing soil pathogens (Vinale et al, 2008) may provide plants with a broader spectrum of physiological functions than each of them alone, potentially having additive or synergistic effects on the growth of their hosts.…”
Section: Introductionmentioning
confidence: 99%